Model of thermal power plant considering water spray desuperheater for power system analysis. (September 2020) - Wen, Libin
Abstract: It is of great significance to build a model of the water spray temperature reduction system that is more suitable for electrical simulation, and apply it to the existing thermal power plant model for the simulation analysis of today's complex thermal power plants. Based on reasonable thermodynamic assumptions, the law of conservation of energy and the law of conservation of mass, a transfer function model of a water-jet cooling system suitable for the simulation of a thermal power plant is established by using mechanism modeling. The relationship between these variables and the effect of each variable on the output variables verified the correctness of the model. A steam turbine system considering the influence of the boiler was further established, and a simulation analysis of the operating characteristics was performed, which verified that the influence of the boiler on the dynamic response of the unit is necessary in the long-term stability analysis. Finally, combined with the model established in this paper, a dynamic model of thermal power unit with water spray temperature reduction device was established. The model is simulated with the step disturbance of velocity, the disturbance of cooling water flow and the disturbance of opening door. Based on the simulation results, the action response characteristics in the process are analyzed. It is verified that the model can accurately describe the main steam parameters and power regulation when applied to large-scale power grid transient simulation.